Transcutaneous Carbon Dioxide Monitoring with Reduced-Temperature Probes in Very Low Birth Weight Infants - Aly, Safwat; El-Dib, Mohamed; Mohamed, Mohamed; Aly, Hany (American Journal of Perinatology, 2017)
Background Obtaining blood gases in very low birth weight (VLBW) infants is an invasive procedure. Studies using transcutaneous carbon dioxide (tcPCO2) have reported variable skin complications with high-temperature probes. No enough data available on tcPCO2 monitoring using reduced-temperature probes (41°C).Objective The objective of this study was to assess reliability and safety of tcPCO2 monitoring at reduced-temperature probe in VLBW infants.Design and Methods A prospective study was conducted on VLBW infants. tcPCO2 was monitored for 12 hours. Default skin probe temperature was adjusted at 41°C. Blood gases were done as clinically indicated. Arterial partial pressure of CO2 (PaCO2) as well as capillary CO2 were compared with simultaneous tcPCO2.Results A total of 124 data points were identified from 50 patients (gestational age [GA] = 28.1 ± 2.4 weeks and birth weight [BW] = 1,035 ± 291 g). Patients were supported with continuous positive airway pressure (40%), noninvasive positive pressure ventilation (16%), mechanical ventilation (18%), and high-frequency oscillation ventilation (24%). PaCO2 was measured using either capillary (58%) or arterial (42%) samples. Mean CO2 did not differ between tcPCO2 (51.3 ± 16) and PaCO2 (49.1 ± 13.7) mm Hg. tcPCO2 showed positive correlation with partial pressure of CO2 (r = 0.6, p < 0.001). This correlation continued to be significant after controlling for GA, postmenstrual age, type of sample, and pH. No skin complications were reported.Conclusion tcPCO2 monitoring using a temperature of 41°C is feasible and reliable in VLBW infants.
Keywords: transcutaneous carbon dioxide; VLBW; premature infants; blood gas